صورة الآخر في الخطاب الروائي لجمال الغيطاني - مقاربة موضوعاتية- - ميسوم عبد القادر (My University, 2011)
On the light of what was made available to the scholar by research methodology, from the liberty through which his introduction is expressed, I say: when we have we have chosen the problematic of the other in the novelistic discourse as a title, it has been done through our intellectual and literary preoccupation. We have started our research with enthusiasm, in spite of our lack of experience since 2002, in our MA project “the Feigning Self and in Modern Arabic Novel. As soon as we tried to bridge the gap between the two milestones, we found ourselves in front of a fact according to which we are yet on the threshold. There is a new way of writing to almost all forms of writing anxiety. The subject matter of this thesis revolves around the following study questions: how does the Other manifest itself in the book of Elghitani? And to what extent does he contribute in the narrative discourse of the story? and if it really calls for adherence to the creative identity? can we considered El Ghitani’s experience, through the data and conditions and manifestations, as a writing of deep authenticity stands at the other end, rejecting any kind of alienation? Today, a novelist like Djamel Ghitani comes out and declares a new birth for the novelistic writing even during the most bitter of the circumstances. This does not mean before him there were no attempts of creative writings, yet they, perhaps, entered into a trance, or was carried by the currents of modernity. This fact has been summed up by Faisal ¨Daradj in the part reserved to the aesthetics of novelistic experimentalism in Djamel Elghitani’s works in his book Theory of the Novel and the Arabic Novel that Mohamed Moulihi wrote in his speech, “The reality of Modern World”, in an inherited language. This is why we tended to explore the topic of our research through its first chapter, “the Disparity of the Other and the Agony of Novelistic Experimentalism”, to decipher the subtle meaning that underlies the text of Elghitani. Starting from the novelistic text in which he displayed his exceptional artistic skills, we explore his invocation of the historical mask in Elziani Berkat, his undertaking of a system of schemes in his second text, The Schemes of Elghitani, and the great impact of this sort of art on the architect ring of the novelistic structures to preserve the memories of place in the imaginary after being annihilated by civilization. Moreover, his book ElTadjaliat, which carries the scent of poetic language that points to the erudite nature of the write who explored the sophist patrimony till enabling discourse to rich the threshold of greatness. As long as the text Tadjaliat recalls other texts in which it is infused aesthetically, we felt obliged to reserve the second chapter for “The Discourse of the Other (manifestations of intertextuality) and to display a short account of the critical conceptualization of the general meaning of intertextuality in old Arabic literary criticism and how it was granted terms which were dominated by the term denoting poetic stealing, plagiarism. To avoid being like police investigators, we gave up this idea while trying to exploit this phenomenon in the writings of a novelist such as Djamel El Ghitani, and specially his sophist texts, namely Elfoutouhat el Mekia and the book of Iben EL Arabi The Tadjaliat